Faktor yang Mempengaruhi Perilaku Pencegahan Kanker Payudara Pada Mahasiswi Kebidanan STIKes Payung Negeri Tahun 2017 - yoneta yoneta (Afiasi : Jurnal Kesehatan Masyarakat, 2019)
Cancer is a condition where cells have lost control and the normal mechanisms, so that experiencing abnormal growth, rapid and uncontrolled. Cases of breast cancer at RSUD Arifin Achmad in 2016 as many 265 people. Case this is a case of breast cancer is highest in the RSUD Arifin Achmad. The purpose of this study was to determine the factors that affect behavior the prevention of breast cancer. This research is descriptive quantitative. This research conducted was on DIII program studi midwifery level I dan II in STIKes Payung Negeri,in july 2017. This research sampel totaled 139 student registered in the STIKes Payung Negeri. The research design was a cross sectional study using questionnaires instrument. Data were analyzed using univariate and bivariate statistical test Chi Square. Results of this study concluded that there was influence of knowledge (p value= 0,001< 0,05) with behavior the prevention of breast cancer, there is no influence of attitude (p value= 0,527>0,05) with behavior the prevention of breast cancer, there is no influence and a history of cancer in the family (p value=0,503>0,05) with behavior the prevention of breast cancer, and there was influence the first age of menarche (p value= 0,007<0,05) with behavior the prevention of breast cancer. The results of this study are recommended for further research, for to follow up on the factors that cause breast cancer, so get better results